Comparison of first-line treatments for elderly patients with diffuse large B-cell lymphoma: A systematic review and network meta-analysis - Wang, Yangyang; Ren, Xiyang; Huang, Keke; Liang, Xue; Pu, Lianfang; Hu, Linhui; Zhai, Zhimin (Frontiers in Immunology, 2023)
Background The incidence of DLBCL in elderly patients has been gradually increased. Considering their comorbidities and performance status, the first-line standard treatment hasn’t been determined for the elderly. Methods We performed a systemic review and network meta-analysis to compare the efficacy and safety of all eligible regimens as first line treatment for elderly patients with DLBCL. We searched PubMed, Cochrane Library, and Embase Library proceedings up to March 2022. Results Our search yielded thirteen trials including 1839 patients. R2CHOP21 showed the best PFS with a statistical difference and the most favorable OS without a statistical difference. RCOMP showed the most clinical benefits in EFS, CR and OR with no significant difference. The point estimate was in favored improved DFS with RCHOP14 than RCHOP21, although this was not statistically significant. In a subgroup analysis concerning 3-4 grade AEs revealed R-COMP was associated with a decrease in grade III/IV neutropenia and cardiac toxic events; RminiCEOP was associated with the lower rates of 3-4 grade anemia, thrombocytopenia and infection; RCHOP21 had the lowest rate of 3-4 grade AE of neurotoxicity. Conclusion The findings of our meta-analysis indicated that R2CHOP21 provided the best disease control in PFS and represented an optimal first-line treatment option in the elderly with DLBCL. Furthermore, RCOMP, RminiCEOP and RCHOP21 exhibited lower rates in different 3-4 grade AEs and might be reasonable treatment options in the elderly with poor general conditions.